The impact of scorecard in operations management course: a case study at the Faculty of Business Management (FPP), UiTM Pahang / Musramaini Mustapha … [et al.] - Mustapha, Musramaini; Muhamed, Mohd Faizal Azrul Azwan; Awang Kader, Mohd Aidil Riduan; Mat Yunus, Nor Khairunnisa; Baharum, Norzie Diana (2015)
Operations Management is a compulsory course for all diploma students of Business Management in Universiti Teknologi MARA (UiTM). This course is taken by two programs in UiTM Pahang: Diploma in Business Studies and Diploma in Banking. The 2012 final examination report indicated a high failure rate of this course at twenty percent. Due to this reason, lecturers have used an alternative method in teaching and learning by introducing the use of scorecard to reduce the failure rate. This scorecard is called Operations Management Performance Scorecard (OMPScard). This study explores the impact of OMPScard orientation among diploma students in the Faculty of Business Management at UiTM Pahang. The results showed a reduced failure rate to less than 3 percent in 2014.